Prevalence, Persistence, and Clinical Significance of Masked Hypertension in Youth - Empar Lurbe; Isabel Torró; Vicente Álvarez; Tim S. Nawrot; Rafael Payá; Josep Redón; Jan A. Staessen (2005)
Masked hypertension, an elevated daytime ambulatory blood pressure in the presence of a normal office blood pressure, confers an increased cardiovascular risk to adults. We investigated the prevalence, persistence, and clinical significance of masked hypertension in children and adolescents. We enrolled 592 youths (6 to 18 years old). Youths with masked hypertension (n=34) and a random sample of the normotensive participants (n=200) were followed-up. In a nested case-control study, we compared echocardiographic left ventricular mass among cases with persistent masked hypertension and normotensive controls. At baseline, mean age was 10.2 years; 535 youths were normotensive on office and daytime ambulatory blood pressure measurement (90.4%), and 45 had masked hypertension (7.6%). Compared with normotensive controls, participants with masked hypertension had a higher ambulatory pulse rate, were more obese, and were 2.5-times more likely to have a parental history of hypertension. Among 34 patients with masked hypertension (median follow-up 37 months), 18 became normotensive, 13 had persistent masked hypertension, and 3 had sustained hypertension. Patients with persistent masked hypertension (n=17) or who progressed from masked to sustained hypertension (n=3) had a higher left ventricular mass index (34.9 versus 29.6 g/m 2.7 ; P =0.023) and a higher percentage with left ventricular mass index above the 95th percentile (30% versus 0%; P =0.014) than normotensive controls. In children and adolescents, masked hypertension is a precursor of sustained hypertension and left ventricular hypertrophy. This condition warrants follow-up and, once it becomes persistent, is an indication for blood pressure-lowering treatment.